Whither Globalism : A World in Crisis? - Wolfensohn, James D. (2017)
James D. Wolfensohn, President of the World Bank Group, discussed the waves of financial crises. He noted the changes in the international scene in recent decades put the current crisis in a different light. The World Bank is trying to help the countries strengthen financial systems; get better accounting systems; and put in bankruptcy laws. The Bank is trying to address the questions of judicial systems. The Bank activities is to focus on the social aspects, to try, and ensure that one can have some basic stability and opportunity to continue with programs of education, health care, training, and address the particular problems of women.